Complete mitochondrial genomes of the charr Salvelinus alpinus erythrinus (Salmoniformes: Salmonidae) from Arctic Canada - Alla G. Oleinik (11992319); Andrey D. Kukhlevsky (11992322); Lubov A. Skurikhina (11992325) (2022)
The complete mitochondrial genomes were sequenced in two individuals of charr Salvelinus alpinus erythrinus from Arctic Canada. The genome sequences were 16,652 bp in length; the genome organization and GC content (45.6%) are consistent with those of charr mitochondrial genomes published previously. The difference between the two genomes studied is low, 0.02%. Our results indicate the phylogenetic closeness of S. alpinus erythrinus and Salvelinus sp. 4 from Lake Nachikinskoe, Kamchatka and their origin from a common ancestor.